An esthetics rehabilitation with computer-aided design/ computer-aided manufacturing technology - Mazaro, José Vitor Quinelli [UNESP]; Mello, Caroline Cantieri de [UNESP]; Zavanelli, Adriana Cristina [UNESP]; Santiago Junior, Joel Ferreira; Amoroso, Andressa Paschoal [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Jaypee Brothers Medical Publishing, 2014)
This paper describes a case of a rehabilitation involving Computer Aided Design/Computer Aided Manufacturing (CAD-CAM) system in implant supported and dental supported prostheses using zirconia as framework. The CAD-CAM technology has developed considerably over last few years, becoming a reality in dental practice. Among the widely used systems are the systems based on zirconia which demonstrate important physical and mechanical properties of high strength, adequate fracture toughness, biocompatibility and esthetics, and are indicated for unitary prosthetic restorations and posterior and anterior framework. All the modeling was performed by using CAD-CAM system and prostheses were cemented using resin cement best suited for each situation. The rehabilitation of the maxillary arch using zirconia framework demonstrated satisfactory esthetic and functional results after a 12-month control and revealed no biological and technical complications. This article shows the important of use technology CAD/CAM in the manufacture of dental prosthesis and implant-supported.
Keywords: Computer aided design/Computer aided manufacturing; Dental prosthesis; Dental implants; Mouth rehabilitation; Case reports